2003
DOI: 10.1023/a:1022861020835
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The activity of choline acetyltransferase (ChAT) was investigated in the human placenta before and after long-term incubation (24 h) to test the effects of sex hormones, nicotine and forskolin. ChAT activity differed considerably between the amnion (0.03 micromol/mg protein/h) and the villus (0.56). After long-term incubation, ChAT activity persisted in the latter but declined in the amnion. Neither sex hormones (beta-estradiol, testosterone, progesterone; 10 or 100 nM each) nor follicle stimulating hormone an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Acetylcholine is synthesized by practically all living cells and can play an intermediary role in the interactions of non neuronal cells with the external environment, hormones, growth factors, cytokines and also the in neural system. On the other hand, all of these factors can also affect the expression and function of the non-neuronal cholinergic system (Wessler et al, 2003;Horiuchi et al. 2003).…”
Section: Non Neuronal Cholinergic Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Acetylcholine is synthesized by practically all living cells and can play an intermediary role in the interactions of non neuronal cells with the external environment, hormones, growth factors, cytokines and also the in neural system. On the other hand, all of these factors can also affect the expression and function of the non-neuronal cholinergic system (Wessler et al, 2003;Horiuchi et al. 2003).…”
Section: Non Neuronal Cholinergic Systemsmentioning
confidence: 99%
“…The mRNA of ChAT and ChAT protein have been demonstrated in isolated human immune cells, airway epithelial cells and cultured human keratinocytes (Grando et al, 1993). It is has been shown that ACh, ChAT, and various mAChRs and nAChRs subtypes are expressed in non-neuronal mammalian tissues and organs, including lymphocytes (Fujii and Kawashima, 2004Kawashima, , 2012, epithelia, gastrointestinal, respiratory and urogenital epithelial cells (Wessler et al 2003) placenta (Sastry, 1997) and vascular endothelial cells (Saeed et al, 2005).…”
Section: Non Neuronal Cholinergic Systemsmentioning
confidence: 99%